Pragmatic Pediatric Trial of Balanced Versus Normal Saline Fluid in Sepsis: The PRoMPT BOLUS Randomized Controlled Trial Pilot Feasibility Study. (18th July 2019) - Balamuth, Fran; Kittick, Marlena; McBride, Peter; Woodford, Ashley L.; Vestal, Nicole; Casper, T. Charles; Metheney, Melissa; Smith, Katherine; Atkin, Natalie J.; Baren, Jill M.; Dean, J. Michael; Kuppermann, Nathan; et al.
Abstract: Background: Resuscitation with crystalloid fluid is a cornerstone of pediatric septic shock treatment. However, the optimal type of crystalloid fluid is unknown. We aimed to determine the feasibility of conducting a pragmatic randomized trial to compare balanced (lactated Ringer's [LR]) with 0.9% normal saline (NS) fluid resuscitation in children with suspected septic shock. Methods: Open‐label pragmatic randomized controlled trial at a single academic children's hospital from January to August 2018. Eligible patients were >6 months to <18 years old who were treated in the emergency department for suspected septic shock, operationalized as blood culture, parenteral antibiotics, and fluid resuscitation for abnormal perfusion. Screening, enrollment, and randomization were carried out by the clinical team as part of routine care. Patients were randomized to receive either LR or NS for up to 48 hours following randomization. Other than fluid type, all treatment decisions were at the clinical team's discretion. Feasibility outcomes included proportion of eligible patients enrolled, acceptability of enrollment via the U.S. federal exception from informed consent (EFIC) regulations, and adherence to randomized study fluid administration. Results: Of 59 eligible patients, 50 (85%) were enrolled and randomized. Twenty‐four were randomized to LR and 26 to NS. Only one (2%) of 44 patients enrolled using EFIC withdrew before study completion. Total median (interquartile range [IQR]) crystalloid fluid volume received during the intervention window was 107 (60 to 155) mL/kg and 98 (63 to 128) mL/kg in the LR and NS arms, respectively (p = 0.50). Patients randomized to LR received a median (IQR) of only 20% (13 to 32) of all study fluid as NS compared to 99% (64% to 100%) of study fluid as NS in the NS arm (absolute difference = 79%, 95% CI = 48% to 85%). Conclusions: A pragmatic study design proved feasible to study comparative effectiveness of LR versus NS fluid resuscitation for pediatric septic shock.